Dibutyryl-cAMP attenuates pulmonary fibrosis by blocking myofibroblast differentiation via PKA/CREB/CBP signaling in rats with silicosis - Liu, Yan (Respir Res, 2017)
BACKGROUND: Myofibroblasts play a major role in the synthesis of extracellular matrix (ECM) and the stimulation of these cells is thought to play an important role in the development of silicosis. The present study was undertaken to investigate the anti-fibrotic effects of dibutyryl-cAMP (db-cAMP) on rats induced by silica. METHODS: A HOPE MED 8050 exposure control apparatus was used to create the silicosis model. Rats were randomly divided into 4 groups: 1)controls for 16 w; 2)silicosis for 16 w; 3)db-cAMP pre-treatment; 4) db-cAMP post-treatment. Rat pulmonary fibroblasts were cultured in vitro and divided into 4 groups as follows: 1) controls; 2) 10(−7)mol/L angiotensin II (Ang II); 3) Ang II +10(−4) mol/L db-cAMP; and 4) Ang II + db-cAMP+ 10(−6) mol/L H89. Hematoxylin-eosin (HE), Van Gieson staining and immunohistochemistry (IHC) were performed to observe the histomorphology of lung tissue. The levels of cAMP were detected by enzyme immunoassay. Double-labeling for α-SMA with Gαi3, protein kinase A (PKA), phosphorylated cAMP-response element-binding protein (p-CREB), and p-Smad2/3 was identified by immunofluorescence staining. Protein levels were detected by Western blot analysis. The interaction between CREB-binding protein (CBP) and Smad2/3 and p-CREB were measured by co-immunoprecipitation (Co-IP). RESULTS: Db-cAMP treatment reduced the number and size of silicosis nodules, inhibited myofibroblast differentiation, and extracellular matrix deposition in vitro and in vivo. In addition, db-cAMP regulated Gαs protein and inhibited expression of Gαi protein, which increased endogenous cAMP. Db-cAMP increased phosphorylated cAMP-response element-binding protein (p-CREB) via protein kinase A (PKA) signaling, and decreased nuclear p-Smad2/3 binding with CREB binding protein (CBP), which reduced activation of p-Smads in fibroblasts induced by Ang II. CONCLUSIONS: This study showed an anti-silicotic effect of db-cAMP that was mediated via PKA/p-CREB/CBP signaling. Furthermore, the findings offer novel insight into the potential use of cAMP signaling for therapeutic strategies to treat silicosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12931-017-0523-z) contains supplementary material, which is available to authorized users.